Why the data gaps in Indian aquaculture need to be addressed to contribute to its efficient and sustainable development - Ramachandran, Rohit; Saito, Osamu; Dam Lam, Rodolfo; Rossignoli, Cristiano (WorldFish, 2023)
Identification of the data gaps can help determine the appropriate methods to improve aquaculture farm operation, production and market access, as well as community capacity. The data gaps can be addressed by creating a national aquaculture database in collaboration with various stakeholders including government bodies, research institutes, private entities, and aquaculture farmers.